2019
DOI: 10.1128/iai.00687-19
|View full text |Cite
|
Sign up to set email alerts
|

The Rho-Independent Transcription Terminator for the porA Gene Enhances Expression of the Major Outer Membrane Protein and Campylobacter jejuni Virulence in Abortion Induction

Abstract: Campylobacter jejuni is a leading cause of foodborne illnesses worldwide. Its porA gene encodes the major outer membrane protein (MOMP) that is abundantly expressed and has important physiological functions, including a key role in systemic infection and abortion induction in pregnant animals. Despite the importance of porA in C. jejuni pathogenesis, mechanisms modulating its expression levels remain elusive. At the 3′ end of the porA transcript, there is a Rho-independent transcription terminator (named TporA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Given that the TOP10 derivatives, JL1371 and JL1381, which carry pmrB-pmrA ORF and pmrB ORF, respectively, displayed the same susceptibility to colistin (MIC = 0.5 µg/mL), the 176 bp downstream sequence of pmrB clearly played a critical role in PmrB-mediated colistin resistance in BL21. It was reported that the 3′-untranslated region (UTR) of a specific gene may form secondary structures, consequently affecting the expression and function of the preceding genes [ 30 , 38 ]. Analysis of 3′-UTR of pmrB using RNAfold WebServer [ 39 ] revealed multiple stem-loop structures ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given that the TOP10 derivatives, JL1371 and JL1381, which carry pmrB-pmrA ORF and pmrB ORF, respectively, displayed the same susceptibility to colistin (MIC = 0.5 µg/mL), the 176 bp downstream sequence of pmrB clearly played a critical role in PmrB-mediated colistin resistance in BL21. It was reported that the 3′-untranslated region (UTR) of a specific gene may form secondary structures, consequently affecting the expression and function of the preceding genes [ 30 , 38 ]. Analysis of 3′-UTR of pmrB using RNAfold WebServer [ 39 ] revealed multiple stem-loop structures ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…Since a significantly low level of pmrB BL21 mRNA was observed in JL1507 when compared to that in JL1509 ( Figure 2 A), the 3′-UTR length may modulate and determine the stability of pmrB BL21 mRNA, as observed in the regulation of other genes [ 30 , 38 ]. To test this hypothesis, the half-life of pmrB in JL1507 and JL1509 was further measured by rifampin arrest treatment followed by qRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations